The Influence of User Involvement and Personal Technical Skills on the Performance of Accounting Information Systems with Work from Home as a Moderator Variable - Mediaty, Mediaty; Said, Darwis; Eleonora, Ellen; Mas’ud, Anis Anshari; Muhammad, Gazali (Journal of International Conference Proceedings, 2023)
This research aims to analyze and demonstrate the influence of user involvement and personal technical skills on the performance of the Accounting Information System (AIS), with Work From Home (WFH) as a moderator variable. The study was conducted at the Financial and Development Supervisory Agency (BPKP) South Sulawesi Representative Office. The sampling technique employed was purposive sampling, and data collection was carried out through the distribution of questionnaires to respondents. Data analysis was conducted using Structural Equation Model Partial Least Square (SEM-PLS). The research findings revealed that user involvement and personal technical skills have a positive and significant impact on AIS performance. However, WFH does not have a significant effect or the ability to strengthen user involvement and personal technical skills in relation to AIS performance. The implications of this research underscore the necessity of user involvement during the development phase of accounting information systems. The study emphasizes the need for training to enhance the understanding and technical skills of accounting information system users.